Recognition and implementation of the smart manufacturing systems in industrial sectors for evolving industry 4.0 - Kler, Rajnish; Ashish; Nimmagadda, Padmaja; Navarajan, J.; Chauhan, Deepak; Babu, Gadde Raghu (Measurement. Sensors, 2024)
The digital twin is referred to as a virtual representation of the physical object and its representation of real-world objects in a virtual manner. The recognition of the digital twin is obtained from real-time data with artificial intelligence techniques. Virtual reality is a three-dimensional environment that enables the users to utilize and explore the virtual environment and is achieved through the combination of hardware and software systems. Augmented reality is enabled in the form of text, audio, and video format representations. It only gets in touch with a combination of the physical and the real world whereas virtual reality proceeds in a frictional world. The increasing usage of smart manufacturing systems using digital twin is providing versatile usages. This incorporates physical and virtual environments and is enabled with the obtained data that helps in the modification of the physical counterpart. Incorporating huge amounts is a bigger challenge, therefore augmented and virtual reality is implemented that helps the users to utilize digital data with higher interest through augmented reality.